Six songs = Szesc piesni : with English and Polish words : 1. To the maiden grieving = Zasmuconej (Op 1)[bladmuziek] - Karlowicz, Mieczyslaw; Sliwinsky, Jan (Glasgow: The Polish Library; Ksaznica Polska)
"Mieczyslaw Karlowicz ; English version by Jan Sliwinski Bibliotheek Camille Huysmans"